1999
DOI: 10.1364/ao.38.006628
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse reflectance spectroscopy of human adenomatous colon polyps in vivo

Abstract: Diffuse reflectance spectra were collected from adenomatous colon polyps (cancer precursors) and normal colonic mucosa of patients undergoing colonoscopy. We analyzed the data by using an analytical light diffusion model, which was tested and validated on a physical tissue model composed of polystyrene beads and hemoglobin. Four parameters were obtained: hemoglobin concentration, hemoglobin oxygen saturation, effective scatterer density, and effective scatterer size. Normal and adenomatous tissue sites exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
461
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 507 publications
(487 citation statements)
references
References 34 publications
14
461
0
2
Order By: Relevance
“…Zonios et al reported a clinical study in which scattering spectroscopy was used to distinguish adenomatous from hyperplastic colonic polyps. 27 Wallace et al employed scattering spectroscopy in the detection of dysplasia within Barrett's esophagus; 28 and Backman et al reported on development of a method using polarized scattering spectroscopy for quantitative assessment of nuclear size in epithelial cells. 29 Diagnostic Applications in Breast Cancer.…”
Section: Elastic Scattering Spectroscopymentioning
confidence: 99%
“…Zonios et al reported a clinical study in which scattering spectroscopy was used to distinguish adenomatous from hyperplastic colonic polyps. 27 Wallace et al employed scattering spectroscopy in the detection of dysplasia within Barrett's esophagus; 28 and Backman et al reported on development of a method using polarized scattering spectroscopy for quantitative assessment of nuclear size in epithelial cells. 29 Diagnostic Applications in Breast Cancer.…”
Section: Elastic Scattering Spectroscopymentioning
confidence: 99%
“…Rid[μs(λ)]=1π2rs2ri2AsdAsAidAiRd[μs(λ)|boldrs-boldri|] where R d is the well-known diffuse reflectance density 26,50 . The integrals here are numerically calculated over the area of the source fiber A s with radius r s and collection fibers A i with radii r i ( i =1, 2).…”
Section: Methodsmentioning
confidence: 99%
“…[19] In vivo measurements of the reflectance spectral data and statistical analysis have been performed in an attempt to detect breast cancers, lesions in ovarian tissues, skin lesions including dysplastic nevi and basal cell carcinomas, and adenomatous colon polyps. [21][22][23][24] Recently, Johnson et al reported the study of spectral reflectance data, between 340 and 900 nm, acquired from 139 cancerous and normal sentinel nodes removed from 68 patients with breast cancers. [25] Statistical analysis of the spectral data yielded scores for discriminating different types of nodes with sensitivity and specificity comparable to those of frozen section histology.…”
Section: Spectroscopy Measurementsmentioning
confidence: 99%